2021
DOI: 10.1371/journal.pone.0247553
|View full text |Cite
|
Sign up to set email alerts
|

What cancer research makes the news? A quantitative analysis of online news stories that mention cancer studies

Abstract: Journalists’ health and science reporting aid the public’s direct access to research through the inclusion of hyperlinks leading to original studies in peer-reviewed journals. While this effort supports the US-government mandate that research be made widely available, little is known about what research journalists share with the public. This cross-sectional exploratory study characterises US-government-funded research on cancer that appeared most frequently in news coverage and how that coverage varied by can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 67 publications
1
11
0
1
Order By: Relevance
“…Other news-focused studies have used Altmetric to not only identify the amount of coverage that research outputs receive but to generate corpora of stories that can later be analyzed to understand how journalists portray those outputs. Using this approach, Moorhead et al ( 2021 ) found that traditional, legacy news sources included significantly more mentions of research on common cancers than digital native news sources. Matthias et al ( 2020 ) used Altmetric data to identify and analyze mentions of research on opioid-related disorders in US and Canadian media, finding that this research was most often portrayed as “valid science”, with little discussion of study methods or limitations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other news-focused studies have used Altmetric to not only identify the amount of coverage that research outputs receive but to generate corpora of stories that can later be analyzed to understand how journalists portray those outputs. Using this approach, Moorhead et al ( 2021 ) found that traditional, legacy news sources included significantly more mentions of research on common cancers than digital native news sources. Matthias et al ( 2020 ) used Altmetric data to identify and analyze mentions of research on opioid-related disorders in US and Canadian media, finding that this research was most often portrayed as “valid science”, with little discussion of study methods or limitations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two-thirds also fail to include a comment from an independent source or expert (Bonevski et al, 2008). Although media reports on CAM and novel biotechnologies can be overly positive, examples of balanced media reporting can be found for conventional biomedical topics, which commonly use findings from research, quantitative data and expert opinion (Amberg and Saunders, 2020; Hallin et al, 2013; Moorhead et al, 2021). For example, the majority of news reporting on genetic research accurately portrays the findings of scientific articles (Bubela and Caulfield, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study trigger the desire of the current researcher to examine how the media cover events of the world cancer day to know if it is enough to generate public awareness creation on cancer related issues in the country. Moorhead et al (2021) in a cross-sectional exploratory study examined the coverage of cancer in newspapers paying attention to how the coverage varied by cancer type, disease incidence and mortality rates. From a total of 11436 research articles (published in 2016) on cancer funded by the US government, the type of cancer that dominated the coverage in the area was cancer of the lung.…”
Section: Empirical Review Of Literaturementioning
confidence: 99%